Implications of providing social support to close network members on the social well-being of older people in Kitui County, Kenya - Mbuthia, Kezia; Mwangi, Samuel; Owino, George (Frontiers in Aging, 2022)
Social support is a strong predictor of social well-being. Older persons are key providers of social support to others but an overemphasis on received social support in gerontological literature portrays them as mere recipients. We, therefore, examined the association between social support provided by older persons and its influence on their social well-being. Data were collected from 369 respondents residing in rural dwellings in Kitui County using mixed methods and were analyzed for association using Chi-square statistics. Instrumental, emotional and information support provision was determined by asking four questions in each regarding whether the respondents provided social support to close network members. The subjective experience of support provision using a satisfaction question for each domain of social support was used to determine the influence of providing social support on the social well-being of older persons. Social support across the three domains was found to be significantly associated with social well-being. The level of statistical significance was highest for emotional and information support compared to instrumental support. Older persons are important providers of social support. The majority of those who provided social support were reported to be satisfied. Therefore, offering social support, especially emotional and information support, is an important contributor to satisfaction with these aspects of social well-being